2001
DOI: 10.1136/adc.85.5.361
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology and clinical presentations of auditory processing disorders---a review

Abstract: Auditory processing disorders may have detrimental consequences on a child's life, if undiagnosed and untreated. We review causes of auditory processing disorders in order to raise clinical awareness. Auditory processing disorders may present against a background of neurological disease or developmental disorders, as well as in isolation. Clinicians need to be aware of potential causes and implications of auditory processing disorders. (Arch Dis Child 2001;85:361-365)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
143
0
31

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(180 citation statements)
references
References 34 publications
6
143
0
31
Order By: Relevance
“…Individuals with APD may report difficulties in understanding speech in the presence of background noise or in the presence of competing messages, in sustaining auditory attention and following oral instructions, or in localizing the sound source. 10,11 However, subjective reports of listening difficulties are not the only problem in individuals with APD, and nearly 50% of the children with APD present with additional language and reading disorders, and only 4% with a 'pure' APD. 12 Correct diagnosis requires multidisciplinary assessments that should include language, reading, cognition, attention, and memory assessments, in addition to different types of auditory processing measures that consist of both non-speech and speech sounds tests (Table SI, published online only).…”
mentioning
confidence: 99%
“…Individuals with APD may report difficulties in understanding speech in the presence of background noise or in the presence of competing messages, in sustaining auditory attention and following oral instructions, or in localizing the sound source. 10,11 However, subjective reports of listening difficulties are not the only problem in individuals with APD, and nearly 50% of the children with APD present with additional language and reading disorders, and only 4% with a 'pure' APD. 12 Correct diagnosis requires multidisciplinary assessments that should include language, reading, cognition, attention, and memory assessments, in addition to different types of auditory processing measures that consist of both non-speech and speech sounds tests (Table SI, published online only).…”
mentioning
confidence: 99%
“…The behavior related to neural plasticity may be predictable, as the plasticity is defined as an changes in nerve cells that occur of according with the environmental influences, that can be controlled and modeled of the desired way 2,14 .…”
Section: Resultsmentioning
confidence: 99%
“…In the first phase, usually around the sixth month of intrauterine life, occurs maturation of the peripheral part of the auditory pathways. In the second phase, which starts after birth and is complete at around 18 months of postnatal life, the auditory pathways become myelinated [1][2][3] . The neural…”
Section: Introductionmentioning
confidence: 99%
“…All these factors were probably present in this population, as already described in the introduction. [16][17][18][19] Differing from BAEPs, in which the auditory pathway is analyzed neuroanatomically and physiologically, the pathway in the behavioral auditory processing tests is analyzed in a functional manner. Thus, the data in both the tests showed that in spite of the unimpaired nature of the auditory pathway, i.e.…”
Section: -35mentioning
confidence: 99%
“…Several studies [16][17][18][19] have investigated possible risk factors for auditory processing disorders. The factors implicated have included histories of ear infections as well as immaturity of the auditory system due to environmental deprivation.…”
Section: Introductionmentioning
confidence: 99%